FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEKURANGAN ENERGI KRONIS PADA IBU HAMIL - febriyeni febriyeni (Universitas Fort De Kock, 2017)
Chronic Energy Deficiency is a situation where the nutritional status someone is on the Less Good Condition. Among the 22 health centers in the district of Lima Puluh Kota, CED highest coverage at the health center are Banja Laweh Namely Case 17 (16.50%) of 103 pregnant mothers. Preliminary Survey of 10 pregnant women at health centers Banja Laweh, note 4 people (40%) of them suffered CED. Based on the findings of interviews stating Not pregnant women know the importance of the size upper arm circumference on Against her pregnancy, in addition to pregnant women consume no food Diversified, because lust Eating Less and Economics not sufficient. Objectives for review determine factors related to the occurrence of Chronic energy deficiency on pregnant women. Methods descriptive analytic with cross sectional approach. Data collection is done on Date in January-February 2017. CASE is a whole population of pregnant women in the region are working Health Center Banja Laweh Year 2017, amounted to 55 people, with sampling total sampling. Operating data analysis using univariate and bivariate statistical test Chi Square. Results of univariate analysis 87,3% of respondents experienced Genesis not CED, (60,0%) High Knowledge, (56,4%) Economy High, and 61,8% of Eating Well. Bivariate analysis known Relationship of Knowledge (p = 0.013 and OR = 12,000, Economics (p = 0.035 and OR = 10,000), and Diet (p = 0.019 and OR = 13,200) with the Genesis CED pregnant women. Can be concluded that the factors related to the occurrence of CED pregnant women is Science, Economics and the Diet. Expected to conduct monitoring of the health center and Supervision of pregnant women at risk Against The Genesis CED, so the negative impact of the CED can be addressed early on.